2013
DOI: 10.1007/s00404-013-3005-7
|View full text |Cite
|
Sign up to set email alerts
|

The necessity of using tenaculum for endometrial sampling procedure with pipelle: a randomized controlled study

Abstract: Endometrial sampling procedure without tenaculum is feasible and yields less pain perception than with tenaculum.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…Although several studies concluded that Pipelle significantly produced less pain than D&C [10,11,12], other studies reported the occurrence of mild-to-severe pain during Pippelle endometrial sampling [13,14,15]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although several studies concluded that Pipelle significantly produced less pain than D&C [10,11,12], other studies reported the occurrence of mild-to-severe pain during Pippelle endometrial sampling [13,14,15]. …”
Section: Discussionmentioning
confidence: 99%
“…VAS was implemented to assess patients' pain. Logistic regression analysis of this study disclosed that the use of cervical tenaculum was an independent risk factor for patients' pain perception [15]. …”
Section: Discussionmentioning
confidence: 99%
“…stated that using the tenaculum increases the risk of painful endometrial sampling procedure 32‐fold. Also, post‐procedure pain scores were found to be higher in the tenaculum group, and they stated that using tenaculum can affect post‐procedure pain perception 6 . Sources of perceived pain are both the cervix grasping and the cervix and uterus pulling.…”
Section: Discussionmentioning
confidence: 99%
“…A pipelle is a 23.5 cm long, flexible polypropylene sheath with an outer diameter of 3.1 mm. An inner plunger is withdrawn, creating suction along a negative pressure gradient 6,8 (Fig. 1).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation